Enhanced radiation response in radioresistant MCF-7 cells by targeting peroxiredoxin II - Diaz AJG (Dove Medical Press, 2013)
Anthony Joseph Gomez Diaz,1 Daniel Tamae,2 Yun Yen,3 JianJian Li,4 Tieli Wang1 1Department of Chemistry and Biochemistry, California State University at Dominguez Hills, Carson, CA, 2Center of Excellence in Environmental Toxicology, Department of Pharmacology, University of Pennsylvania, Philadelphia, PA, 3Department of Clinical and Molecular Pharmacology, Beckman Research Institute of City of Hope National Medical Center, Duarte, CA, 4Department of Radiation Oncology, University of California Davis, Sacramento, CA, USA Abstract: In our previous study, we identified that a protein target, peroxiredoxin II (PrxII), is overexpressed in radioresistant MCF+FIR3 breast-cancer cells and found that its expression and function is associated with breast-cancer radiation sensitivity or resistance. Small interference RNA (siRNA) targeting PrxII gene expression was able to sensitize MCF+FIR3 radioresistant breast-cancer cells to ionizing radiation. The major focus of this work was to investigate how the radiation response of MCF+FIR3 radioresistant cells was affected by the siRNA that inhibits PrxII gene expression. Our results, presented here, show that silencing PrxII gene expression increased cellular toxicity by altering cellular thiol status, inhibiting Ca2+ efflux from the cells, and perturbing the intracellular Ca2+ homeostasis. By combining radiotherapy and siRNA technology, we hope to develop new therapeutic strategies that may have potential to enhance the efficacy of chemotherapeutic agents due to this technology's property of targeting to specific cancer-related genes. Keywords: siRNA, PrxII, radiation resistance, Ca2+, MCF+FIR3